Formal Organizations : a comparative approach - Blau, Peter M., 1918-2002.; Scott, W. Richard (California : Chandler Publishing Company, 1962)
"In the book, the authors reviewed multiple types of studies - including case studies, experimental research, and surveys - and integrated them to define new central themes. They used their own empirical studies of two social welfare agencies to illustrate the ways in which varying organizational contexts shape work group and participant attitudes and activities. Formal Organizations served to integrate research on both formal and informal systems, authority and leadership, and stressed the importance of links to the wider environment. This reissue, which includes a new introduction by Scott, makes this seminal work accessible to a new generation of scholars and practitioners."--BOOK JACKET.
1. Introduction -- 2. The Nature and Types of Formal Organizations -- 3. The Organization and Its Publics -- 4. The Social Structure of Work Groups -- 5. Processes of Communication -- 6. The Role of the Supervisor -- 7. Managerial Control -- 8. The Social Context of Organizational Life -- 9. Organizational Dynamics -- App. Description and Comparison of the Two Welfare Agencies.
Includes bibliographical references (p. 258-301) and indexes.
Keywords: Comparative organization; Associations, institutions, etc